Detection of Mycobacterium bovis–infected dairy herds using PCR in bulk tank milk samples - Zumarraga, Martin Jose (2012)
Bovine tuberculosis (bTB) is a chronic and zoonotic disease due to Mycobacterium bovis. The tuberculosis eradication campaign carried out in Argentina has considerably improved the health situation of the herds. Here we evaluated a strategy to detect M. bovis–infected herds by Touch-Down IS6110 polymerase chain reaction (PCR) in bulk tank raw milk from dairy farms. We evaluated 177 samples from herds with the official tuberculosis free certificate (TFC) and 80 from herds without the certificate, non-tuberculosis-free certificate (NTFC), from 10 departments of Santa Fe province, Argentina. To avoid the effect of Taq polymerase inhibitors, a dilution of DNA template was performed. Positive PCR results were obtained in 102 (40%) of the samples, whereas negative ones were obtained in 155 (60%) of the samples. Importantly, 44% of NTFC and 38% of TFC samples were positive. All samples were subjected to culture in Löwenstein Jensen and Stonebrink media with no positive isolation. The negative predictive value (NPV) of PCR in the TFC group was 95%, while the positive predictive value (PPV) of PCR in the NTFC group was 51%. Based on these results, this work proposes a method that should be applied regularly to detect M. bovis--infected dairy herds, complementary to the official test of tuberculin, or purifed protein derivative (PPD), to control dairy herds, especially those free of tuberculosis.